Screening for Cognitive Dysfunctions in Patients with Combined Hashish and Tramadol Addiction (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: screening; MOSA test; cognitive dysfunction; poly addiction; combined addiction; hashish; tramadol